Electromagnetic geophysical fields : precursors to earthquakes and tsunamis ; impacts on the brain and heart /: precursors to earthquakes and tsunamis ; impacts on the brain and heart. ([2019]) - Novik, Oleg; Smirnov, Ḟeodor; Volgin, Maxim
No abstract available